Poškodbe s traktorji in obdelovalnimi stroji pri otrocih - Primožič, Janez (Zdravniški vestnik, 2006)
We analysed injuries in children caused by tractors and other agricultural machinery. Retrospective overview of health records of children admitted to hospital between 1 January, 2001, and 31 December, 2004. We found 45 children,aged 7.2 years on average (SD 2.3, range 17 months - 14 years). Therewere 39 boys (87%) and 6 (13%) girls. The injuries were caused by tractorin 28 (62%) children; the children were involved in the accidents as passengers on farming cart in 4 (10%) cases, when moving around otherfarming vehicles in 8 (16%) cases, and when moving around small farming machines or using farming tools in 5 (10%) cases. There were 19 (42%) light injuries, 20 (44%) severe ones, and 6 (14%) very severe injuries Thirty-three (73%) children sustained injuries of multiple body parts. Head injury was sustained by 23 (51%) children. Average length ofstay in the hospital was 8.5 days, (SD 23; range 1-133). All the children survived the accident. Tractors and other agricultural machinery are apossible source ofsevere injuries in children. In general, several parts of the body are injured simultaneously. Mostly, the head is affected. Compared to other agriculturally developed countries, such injuries are more frequentin Slovenia. Adequate prevention is the key to avoiding this type of injuries.
Keywords: Agriculture; Child; kmetijski stroji; kmetijstvo; nezgode; otroci; Otrok; Poljedelstvo; poškodbe; rane; Rane in poškodbe; Technology; Tehnologija; Wounds And Injuries